2014
DOI: 10.5117/cms2014.3.bilg
|View full text |Cite
|
Sign up to set email alerts
|

Migrants’ Multi-Sited Social Lives

Abstract: This paper challenges the assimilationist assumption that suggests migrants cannot be simultaneously embedded in multiple societies. Based on survey data collected among Afghan, Burundian, Ethiopian and Moroccan migrants in the Netherlands, the paper shows that overall sociocultural integration in the Netherlands and sociocultural homeland engagement are significantly positively correlated. Moreover, it demonstrates that migrants with more contact with their co-ethnics in the Netherlands tend to engage more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…Furthermore, engagements can be in a positively or negatively reinforcing relationship. Considering this typology, recent studies have found evidence about the positive relationship between host society integration and transnational involvement (Bakker et al, 2014;Bilgili, 2014;Kuuire et al, 2016;Levitt & Glick Schiller, 2004;Schunck, 2014;Şimşek, 2018;Snel et al, 2006;Van Bochove et al, 2010). However, there is also some evidence on their competing nature (Ley, 2013).…”
Section: Determinants Of Transnational Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, engagements can be in a positively or negatively reinforcing relationship. Considering this typology, recent studies have found evidence about the positive relationship between host society integration and transnational involvement (Bakker et al, 2014;Bilgili, 2014;Kuuire et al, 2016;Levitt & Glick Schiller, 2004;Schunck, 2014;Şimşek, 2018;Snel et al, 2006;Van Bochove et al, 2010). However, there is also some evidence on their competing nature (Ley, 2013).…”
Section: Determinants Of Transnational Involvementmentioning
confidence: 99%
“…In Snel et al's (2006) study, 74% of migrants reported reading newspapers from their country of origin. Recent studies have argued (Bilgili, 2014;Bloch, 2008;Chaudhary, 2018) that political activities can be seen as complementary: if one is active in politics, they tend to be active in both their country of origin and the new host country.…”
Section: How Common Is Transnational Involvement?mentioning
confidence: 99%
“…This special issue introduces a third pillar of research on how migration relates to social networks by focusing on the role of migrants' transnational networks in shaping migration trajectories. Firstly, we recognise that many migrants are embedded in transnational social fields in today's networked societies (Bilgili 2014). That is to say, their social interpersonal relations are not bound to a single space and their lives span across borders.…”
Section: Transnational Social Support In Migrant Trajectoriesmentioning
confidence: 99%
“…Op dezelfde wijze heb ik de verbanden onderzocht tussen socioculturele integratie en sociale relaties die worden onderhouden met familie en vrienden in het land van herkomst. Mijn onderzoek laat zien dat er niet genoeg bewijs is om te stellen dat er een negatief verband bestaat tussen de twee (Bilgili 2014). Het hebben van meer contact met de Nederlandse samenleving door middel van recreatieve activiteiten vertoont bijvoorbeeld geen negatieve relatie met betrokkenheid bij socioculturele activiteiten die zijn gericht op het land van herkomst.…”
Section: Levens Die Grensoverschrijdend Zijn Ingebed En Verschillendeunclassified
“…Wanneer migranten het gevoel hebben dat ze in het bestemmingsland een stabiele rechtspositie hebben, en niet bang zijn om hun recht om terug te keren naar hun bestemmingsland kwijt te raken, reizen ze vaker terug naar hun land van herkomst. Het hebben van een dubbele nationaliteit vertoont een significant positief verband met het terugreizen, vergeleken met het hebben van slechts één nationaliteit (Bilgili 2014). Een dubbele nationaliteit is met andere woorden sterk gerelateerd aan meer mobiliteit, waardoor migranten tegelijkertijd in meerdere contexten kunnen zijn ingebed.…”
Section: Het Koppelen Van Integratie-en Ontwikkelingsbeleid: Betrokkeunclassified